Plasma Levels of CGRP During a 2-h Infusion of VIP in Healthy Volunteers and Patients With Migraine: An Exploratory Study - Pellesi, Lanfranco; Al-Karagholi, Mohammad Al-Mahdi; De Icco, Roberto; Chaudhry, Basit Ali; Lopez, Cristina Lopez; Snellman, Josefin; Hannibal, Jens; Amin, Faisal Mohammad; Ashina, Messoud (Frontiers in Neurology, 2022)
Introduction The activation of perivascular fibers and the consequent release of vasoactive peptides, including the vasoactive intestinal polypeptide (VIP), play a role in migraine pathogenesis. A 2-h infusion of VIP provoked migraine, but the mechanisms remain unknown. We investigated whether 2-h infusion of VIP caused alterations in plasma levels of the calcitonin gene-related peptide (CGRP) and whether any changes might be related to the induced migraine attacks. Materials and Methods We enrolled individuals with episodic migraine without aura and healthy participants to randomly receive a 2-h infusion of either VIP (8 pmol/kg/min) or placebo (sterile saline) in two randomized, placebo-controlled crossover trials. We collected clinical data and measured plasma levels of VIP and CGRP at fixed time points: at baseline (T0) and every 30 min until 180 min (T180) after the start of the infusion. Results Blood samples were collected from patients with migraine (n = 19) and healthy individuals (n = 12). During VIP infusion, mixed effects analysis revealed a significant increase in plasma CGRP (p = 0.027) at T30 (vs. T180, adjusted p-value = 0.039) and T60 (vs. T180, adjusted p-value = 0.027) in patients with migraine. We found no increase in plasma CGRP during VIP-induced migraine attacks (p = 0.219). In healthy individuals, there was no increase in plasma CGRP during VIP (p = 0.205) or placebo (p = 0.428) days. Discussion Plasma CGRP was elevated in patients with migraine during a prolonged infusion of VIP, but these alterations were not associated with VIP-induced migraine attacks. Given the exploratory design of our study, further investigations are needed to clarify the role of CGRP in VIP-induced migraine. Clinical Trial Registration ClinicalTrials.gov, identifier: NCT03989817 and NCT04260035.